Geospatial Distribution of Family Planning Services in Kira Municipality, Wakiso District, Uganda - Tetui, Moses; Ssekamatte, Tonny; Akilimali, Pierre; Sirike, Judith; Fonseca-Rodríguez, Osvaldo; Atuyambe, Lynn; Makumbi, Fredrick Edward (Frontiers in Global Women's Health, 2021)
Introduction:Access to family planning services remains a challenge particularly in urban informal settlements. The unmet need for family planning in these settlings is high with correspondingly high prevalence of unintended pregnancies that may lead to unsafe abortions. However, there is paucity of quality data on the distribution of family planning services in such settings in Uganda. The paper described the geospatial distribution of family planning services in Kira Municipality, Wakiso District, Uganda. Methods:A cross sectional study determined the availability and distribution of family planning services in the informal settlements. Community mapping and analysis were conducted using ArcGIS (version 10.1) and ArcGIS Online. STATA version 13.0 was used for quantitative data analysis. Chi-square test was used to compare facilities found in the informal and formal settlements. Results: Of the 176 healthcare facilities were surveyed, only 42% (n=74) offered contraceptives in the informal settlements. Majority of the facilities were privately owned small clinics (95%). At least 80% of the facilities provided three or more modern contraceptive methods, with no difference (Chi2 2.6044, p=0.107) between facilities in informal and in formal settlements. Only 30.7% (chi2 10.3253, p=0.001) of the facilities provided at least one long acting contraceptive. Similarly, 22.7% (chi2 10.3244, p=0.001) of the facilities had at least one long acting contraceptive on the day of the survey. Almost 25% of the facilities did not offer contraceptive services (counseling and commodities) to unmarried adolescents. Conclusions: The majority of facilities were small privately-owned clinics. Most of the facilities provided at least three more modern contraceptive methods. However, very few provided and had at least one long lasting contraceptive on the day of the survey, this could indicate a poor method mix, thus limiting the choice of users, moreover, the situation was worse among facilities found in informal settlements. This points to probable deficit in the contraceptive commodities in Kira municipality, thereby limiting use. Additionally, access of services to unmarried adolescents could be limited by providers who deny them service. A call to local government and partners to fill the commodities gap and discrimination against adolescents will be essential.